2019
DOI: 10.1002/ptr.6375
|View full text |Cite
|
Sign up to set email alerts
|

Schisandra chinensis extract ameliorates age‐related muscle wasting and bone loss in ovariectomized rats

Abstract: Exercise and healthy diet consumption support healthy aging. Schisandra chinensis (Turcz.) also known as “Baill.” has anti‐inflammatory and antioxidant properties. However, the role of S. chinensis as an antiaging compound has yet to be demonstrated. This study elucidated the antiaging effect of S. chinensis ethanol–hexane extract (C1) and the effect of C1 treatment on muscle and bone following physical exercise in ovariectomized (OVX) rats. RAW 264.7, human diploid fibroblasts (HDFs), C2C12 myoblasts, bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In ovariectomized rats, SC treatment combined with exercise alleviated sarcopenic muscle wasting and enhanced muscle regeneration in skeletal muscle by promoting mitochondrial biogenesis and autophagy. In the same study, which used an in vitro model, SC significantly reduced the expression of inflammatory markers and β-galactosidase activity while improving the antioxidant defenses by decreasing ROS levels [ 142 ]. Furthermore, in forced-swimming exercise-induced aged mice, SC effectively increased the strength and thickness of the GM and soleus muscles.…”
Section: Polyphenols In Managing Muscle Atrophy and Muscle Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In ovariectomized rats, SC treatment combined with exercise alleviated sarcopenic muscle wasting and enhanced muscle regeneration in skeletal muscle by promoting mitochondrial biogenesis and autophagy. In the same study, which used an in vitro model, SC significantly reduced the expression of inflammatory markers and β-galactosidase activity while improving the antioxidant defenses by decreasing ROS levels [ 142 ]. Furthermore, in forced-swimming exercise-induced aged mice, SC effectively increased the strength and thickness of the GM and soleus muscles.…”
Section: Polyphenols In Managing Muscle Atrophy and Muscle Healthmentioning
confidence: 99%
“…Mainly, the E3 ubiquitin ligases atrogin-1, MuRF-1, and/Cbl-b were suppressed by PPs in muscle atrophies caused by inflammation, oxidative stress, and mitochondrial damage. The upstream regulators of E3 ubiquitin ligases, i.e., TNF-α, IL-6, IL-1β, NF-κB, myostatin, and FoxOs, were significantly suppressed by PPs [ 32 , 38 , 79 , 96 , 127 , 142 , 151 ]. Moreover, PPs modulated the expression of miRNAs associated with muscle atrophy.…”
Section: Critical Overview and Future Perspectivesmentioning
confidence: 99%
“…The fruits contain many bioactive compounds, including lignans, triterpenes, phenolic acids, flavonoids, essential oils, and polysaccharides [ 3 , 4 ], and they have been used as an important traditional medicine in northeastern Asia. In particular, dibenzocyclooctadiene lignans, including schisandrin and gomisin, present in S. chinensis fruit extracts exhibit pharmacological effects such as antitumor, anti-inflammatory, antioxidative, hepatoprotective, antihypertensive, and anti-osteoporosis activities [ 3 7 ]. Moreover, fruits have the potential to effectively protect against neuronal cell damage and to significantly enhance cognitive performance, suggesting their usefulness as new therapeutic agents for treating neurodegenerative diseases [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies have reported therapeutic effects of SC on blood sugar balance, wound healing, alleviating cough, liver injury, kidney injury, lung injury, platelet aggregation hepatitis, and cardiovascular disease [16,20]. SC has also been reported to prevent age-related disease such as osteoporosis and sarcopenia [21]. In a study on cyclophosphamide-induced dyszoospermia in male rats, Schizandra chinensis polysaccharide could alleviate reproductive hormones and improve fertility [22].…”
Section: Introductionmentioning
confidence: 99%